Performance evaluation of collection tree protocol (CTP) for mobile wireless sensor network (MWSN) - Farha Anati, Ahmad Mansor (Universiti Malaysia Sarawak (UNIMAS), 2013)
Nowadays, Mobile WSN application is growing over widely. However, mobility gives many challenges to the routing protocols used in such application. In this simulation-based project, the performance of Collection Tree Protocol (CTP) is evaluated in the mobile environment. From the simulation and study, it shows that CTP perform poorly in mobile environment because of the frequent tree re-generation resulting from the node movement. In this project, the performance of CTP in static and mobile environmental also will be analyzed to identify factors that contribute to the degradation of CTP's performance in mobile environment.